UPAYA PENINGKATAN KINERJA YANG BERORIENTASI KEMITRAAN LINGKUNGAN PESISIR DI KABUPATEN REMBANG GUNA MENDUKUNG PENGEMBANGAN UMKM PENGOLAHAN IKAN (STIE YPPI Rembang, 2014)
AbstractThis study aims to the development of SMEs in the fish processing Rembang with increased performance. The real reality in society SMEs development of fish processing in Rembang hampered by the low level of performance of its employees due to many factors. Therefore, this research proves the effect of the increase in performance of the SMEs development in the fish processing Rembang moderated by variable partnerships. This study is expected to get an idea of the concrete forms and types of fish processing SMEs partnership in Rembang which can be used as a reference for performance improvement in the development of SMEs. Criteria respondent SMEs fish processors in the northern coastal path Rembang is Kaliori, Rembang, Lasem, Sluke, Kragan and Sarang. SMEs fish processing workers who have a maximum of 5 orang.Uji instruments carried on the 30 respondents with the results of all valid and reliable. Technical analysis of the data using moderated regression analysis. The number of respondents based criteria 115 SMEs.Â Keyword: Performance Improvement, OrientationPartnership, SMEsDevelopment.Â